Depression Among Immigrant Nigerians in Canada - Aluh, Deborah Oyine; Aigbogun, Osaro; Anyachebelu, Obinna Chkwudi (Kluwer Academic/Plenum Publishers, 2022)
Immigrant status, especially a few years post arrival, is a major risk factor for depression in populations that have been adequately studied. While information on depression among Asian migrants, including those from India, China and Philippines, in Canada have been reported in previous studies, there is inadequate information about depression among Nigerian immigrants who make up the largest percentage of African migrants and black population residing in Canada. A cross-sectional study was conducted among 187 Nigerian immigrants in Canada. Participants completed the Patient Health Questionnaire (PHQ-9). Descriptive and multivariate logistic regression analyses were carried out using IBM SPPS. About half (51.7%, n = 91) of the participants screened positive to the PHQ-9. Being female, unmarried, not being at all satisfied with the decision to migrate, and having stayed for more than 10 years in Canada significantly increased the risk of screening positive to depression. More than half of the participants screened positive for depression, suggesting an important mental health concern and the potential need for intervention. This population differed from other immigrant populations from previous studies because the absence of social support, satisfaction with employment status, and perceived discrimination did not significantly predict a positive screen for depression in this study.